Adolescent agency and behavioral characteristics: conformity, problematic behavior, need for cognition - Goshin, Mikhail; Grigoryev, Dmitry; Sorokin, Pavel (Frontiers in Psychology, 2025)
The concept of human agency has attracted considerable interest in academic and expert discussions concerning various life domains and age groups, including adolescents. However, the field lacks a unified approach to measuring agency for adolescents and understanding its relationship with their behavioral characteristics and attitudes. This study addresses these gaps by introducing an Adolescent Agency Index and examining its associations with behavioral characteristics such as сonformity, problematic behavior, and the need for cognition. The data was collected from students in grades 4 to 8 (N = 4,603; Mage = 12.6, SD = 1.7; 50.3% female). The analyses indicated a negative relationship between agency and conformity and a positive relationship between agency and problematic behavior; moreover, a stronger positive relationship was found with the need for cognition. At the same time, the nature of the relationship between agency and these characteristics is complex, non-linear. These findings provide valuable insights for educational policymakers, researchers, and families.